Occurrence and partitioning behavior of per- and polyfluoroalkyl substances (PFASs) in water and sediment from the Jiulong Estuary-Xiamen Bay, China. (January 2020) - Wang, Siquan; Ma, Liya; Chen, Can; Li, Yongyu; Wu, Yuling; Liu, Yihao; Dou, Zhiyuan; Yamazaki, Eriko; Yamashita, Nobuyoshi; Lin, Bin-Le; Wang, Xinhong
Abstract: Twenty-four per- and polyfluoroalkyl substances (PFASs) were analyzed in water and sediment from the Jiulong Estuary-Xiamen Bay to study their seasonal variations, transport, partitioning behavior and ecological risks. The total concentration of PFASs in water ranged from 11 to 98 ng L −1 (average 45 ng L −1 ) during the dry season, 0.19–5.7 ng L −1 (average 1.5 ng L −1 ) during the wet season, and 3.0–5.4 ng g −1 dw (average 3.9 ng g −1 dw) in sediment. In water samples, short-chain PFASs were dominated by perfluorooctanoic acid (PFBA) in the dry season and perfluorobutane sulfonate (PFBS) in the wet season, while long chain PFASs, such as perfluorooctane sulfonate (PFOS), dominated in the sediment. The highest concentration of PFASs in water were found in the estuary; in contrast, the highest level of PFASs in sediment were found in Xiamen Bay. These spatial distributions of PFASs indicate that river discharge is the main source of PFASs in estuarine water, while the harbor, airport and wastewater treatment plant near Xiamen Bay may be responsible for the high PFBS and PFOS concentrations in water and sediment. The partition coefficients (log Kd ) of PFASs between sediment and water (range from 1.64 to 4.14) increased with carbon chain length (R 2  = 0.99) and also showed a positive relationship with salinity. A preliminary environmental risk assessment indicated that PFOS and perfluorooctanoic acid (PFOA) in water and sediment pose no significant ecological risk to organisms. Highlights: Concentrations and compositions of PFASs in the JEXB had significant seasonal variations. Short chain PFASs were dominated in water. Long chain PFASs were high in sediment. PFBA as an alternative increased in water compared with our previous data. The river discharge, airport, harbor and wastewater treatment plant were the most important sources. Log Kd of PFASs increased with the increasing carbon chain length and salinity.